Pseudoexfoliation syndrome: The critical role of the extracellular matrix in pathogenesis and treatment. Issue 10 (24th February 2022) - Mastronikolis, Stylianos; Pagkalou, Marina; Baroutas, Giorgos; Kyriakopoulou, Konstantina; Makri, Οlga E.; Georgakopoulos, Constantinos D.
Abstract: Pseudoexfoliation syndrome (PEXS) is an age‐related condition manifesting mainly in ocular tissues. PEXS is manifested through excess aggregation of fibrillary extracellular material at the anterior part of the eye that consists of a plethora of biomolecules, such as different proteoglycans (PGs) and glycosaminoglycans. PEXS is often linked to increased intraocular pressure, and can also lead to pseudoexfoliation glaucoma with very poor prognosis. Various stimuli are known to affect PEXS, including oxidation stress (OS), UV radiation and osmotic pressure. OS, is prominently involved on the progression of the syndrome as it promotes fibrogenesis, possibly via the induction of transforming growth factor‐β (TGF‐β) and other biomolecular effectors. In addition, PEXS initiation is tightly connected with the dysregulation of extracellular matrix (ECM) homeostasis since aberrant expression of ECM molecules is linked to both the accumulation and low degradation of pseudoexfoliation material. This article aims at uncovering the crucial role of various ECM effectors such as lysyl oxidase‐like proteins, matrix metalloproteinases, and TGF‐β1, as well as the biochemical pathways involved in the development and the progression of the PEXS.